Assertive behaviour difference among domestic violence victims - Anisa Dwi Astuti; Alizamar Alizamar; Afdal Afdal (Journal of Educational and Learning Studies, 2019)
n 2017, the number of cases related to violence against women increased by  400% from the previous year. This research, therefore, aims to analyze behavior difference among domestic violence victims using a quantitative descriptive method. Data were obtained from 64 victims using a Likert scale, while the descriptive techniques and T-Test analysis were used to examine the data obtained. The results showed that the assertive behavior of women victims of domestic violence without elementary education was lower compared to those with junior, high, and college education.